Penalty Imposed On Debt Payment Delaying-Capable-Clients: A Study on DSN-MUI’s Fatwa No. 17/DSN-MUI/IX/2000 - Maftukhatusolikhah Maftukhatusolikhah (Jurnal Iqtisad, 2003)
Islamic banking is an obvious sample of Islamic economic system implementation, and hence, problems around Islamic banks are interesting to study.  As a system differing from conventional, both in terms of ontology and epistemology, Islamic banking is expected to be able to offer a truly Islamic system that is in line with the Quran and Sunnah. Therefore, if any problems emerge on it, the solutions will be determined according to Islamic law.One of the problems faced by Islamic banking is the handling of debt payment delay-ing-capable-clients. Delaying debt payment is an action if permitted to continue will dis-turb bank’s productivity and, indirectly, Islamic banking system as a whole. Moslem schol-ars have different positions on this matter. National Shariah Council of Indonesian Coun-cil of Ulema (DSN-MUI) and several individual jurists contend that it is necessary to pe-nalize debt payment delaying-capable-clients with the obligation to compensate material loss as “overdue fine”. Several other jurists however argue the penalty as it is considered similar to forbidden riba, whereas the main argument (raison d’etre) for the establishment of Islamic banking is itself to avoid this kind of riba. Hence, legal-normative perspective in handling debt payment delaying-capable-clients is very interesting to study.